Perspectives of healthcare providers on telemedicine implementation during the COVID-19 pandemic in Colombia: a mixed-method study - Susana Orrego Villegas; Susana Orrego Villegas; Susana Orrego Villegas; Eric Adjei Boakye; Jafet Arrieta; Jafet Arrieta; Jafet Arrieta; Karine Posada España; Karine Posada España; Melisa Naranjo Vanegas; Gloria Pardo Pino; Gloria Pardo Pino; et al. (Frontiers in Public Health)
BackgroundThe COVID-19 pandemic accelerated the adoption of telemedicine (TM) in Colombia as a tool for delivering healthcare for both chronic and non-chronic conditions. This study aimed to explore the perspectives of healthcare providers, directors, and managers on TM implementation within a major health plan provider covering 15% of the Colombia population.MethodsMixed-methods study was conducted, combining surveys and in-depth interviews with medical professionals and decision-makers. Thematic analysis of qualitative data and statistical analysis of survey responses provided insights into the challenges and opportunities of TM during the pandemic.ResultsHealthcare providers recognized TM as a valuable tool but identified key challenges to its optimization. Three main strategies were proposed: (1) enhancing medical training to improve remote diagnosis, (2) integrating wearables and digital technologies to support clinical decision-making, and (3) fostering a culture of TM use among patients and providers to ensure acceptance and sustainability.ConclusionTelemedicine facilitated equitable healthcare delivery and contributed to reducing the digital gap in Colombia. However, to ensure long-term viability, national policies must improve internet connectivity and strengthen primary care infrastructure, particularly in underserved regions.